Design and failure modes of a standard railway catenary cantilever support. (January 2020) - Rechena, D.; Infante, V.; Sousa, L.; Baptista, R.
Highlights: A industrial case for the Portuguese railway infrastructure was developed. A methodology is presented towards the mechanical design of standard components. Static and linear fracture mechanics analysis was performed. A design problem was made considering the function aggregation in components. Abstract: Infrastructure managers of small railways have limited action lines with respect to product development of maintenance components. In many cases, they have a significant number of different components in their operation railway lines. Therefore, they have a poor bargaining power when it comes to ordering components for the railway infrastructure due to small ordering volumes. In addition, a large number of components has to be produced and stored to answer the needs of the operation and maintenance, increasing the overall costs. An approach to reduce the mentioned problems is standardization, which comes as a solution to reduce lifecycle costs due to benefits such as increased production volumes, longer learning curves in manufacturing, maintenance and reduced stock levels. In this paper a set of standard cantilever supports for the railway catenary system were developed thus replacing a set of supports with different designs for similar functions. These components are of critical importance since they are responsible for transmitting the entirety of the pre-loads, as well as train dynamic loads, of the catenary system to the supporting poles. The new proposed solution was modelled and analysed using NX Nastran and ABAQUS simulation tools with contact detection between components. The finite element analyses covered the static behaviour as well as the linear fracture mechanics of cracks in critical areas of the designed cantilever supports. The linear fracture results were also used to estimate the fatigue life of the cantilever supports. The loads were modelled for train speeds of up to 300 km/h. The results indicate that the most likely failure mode is fatigue crack propagation in one of the critical areas of the lower cantilever support under tension with a fatigue life of 8224 load cycles. Due to the low fatigue life of the nodular cast iron GJS-400-15, the B319-T7 and A356-T6 aluminium alloys were also considered, resulting in fatigue lives of 375, 990 and 1, 093, 500 cycles, respectively.